2016
DOI: 10.1002/chem.201505055
|View full text |Cite
|
Sign up to set email alerts
|

Methylammonium Bismuth Iodide as a Lead‐Free, Stable Hybrid Organic–Inorganic Solar Absorber

Abstract: Methylammonium lead halide (MAPbX3 ) perovskites exhibit exceptional carrier transport properties. But their commercial deployment as solar absorbers is currently limited by their intrinsic instability in the presence of humidity and their lead content. Guided by our theoretical predictions, we explored the potential of methylammonium bismuth iodide (MBI) as a solar absorber through detailed materials characterization. We synthesized phase-pure MBI by solution and vapor processing. In contrast to MAPbX3, MBI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
339
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 333 publications
(362 citation statements)
references
References 41 publications
22
339
0
1
Order By: Relevance
“…47 Challenges also exist in performing quantum mechanical calculations on some of these materials. These calculations are used to predict the thermodynamically stable crystal structure for a given composition, 21 and are also often used to predict the electronic structure. 27,28,30,31 As suggested by recent literature, these calculations have become a critical component in the search for novel photovoltaic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Challenges also exist in performing quantum mechanical calculations on some of these materials. These calculations are used to predict the thermodynamically stable crystal structure for a given composition, 21 and are also often used to predict the electronic structure. 27,28,30,31 As suggested by recent literature, these calculations have become a critical component in the search for novel photovoltaic materials.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,30,31 As suggested by recent literature, these calculations have become a critical component in the search for novel photovoltaic materials. 17,20,21,25,28,30,31,48,49 However, the layered structure and presence of partially-oxidized heavy metal cations in many of these materials necessitate special care when performing these calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[5,9,[11][12][13] Timecorrelated single photon counting (TCSPC) measurements of (CH 3 NH 3 ) 3 Bi 2 I 9 and Cs 2 AgBiBr 6 , among others, have shown that these materials exhibit lifetimes exceeding 1 ns. [11,15,16] This is significant because analysis of established thin-film solar absorbers has shown that materials with minority-carrier lifetimes of 1 ns or above have the potential to reach or exceed 10% efficiency. [17] Many of these bismuth halides and chalcohalides have also demonstrated improved air-stability compared to hybrid lead-halide perovskites.…”
mentioning
confidence: 99%
“…[17] Many of these bismuth halides and chalcohalides have also demonstrated improved air-stability compared to hybrid lead-halide perovskites. [11,13,15] However, devices based on these materials have low reported power conversion efficiencies under AM 1.5G illumination, between 0.1 and 1.2%. [1] The short-circuit current densities (J SC , <4 mA cm −2 ) and external quantum efficiencies (EQEs, <60%) have also been poor, [1,18] in spite of efforts to extend the photoconversion range of bismuth halide semiconductors (J SC < 3.4 mA cm −2 , EQE < 25%).…”
mentioning
confidence: 99%
See 1 more Smart Citation